The Influence of Board of Directors Characteristics on Corporate Financial Distress - Sri Purwaningsih; Rista Bintara; Siti Sarpingah (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study is based on complementary proposals between agency theory based on the behavioral characteristics of the board of directors. The research examines whether gender diversity on the board, board size, expertise, and board compensation costs affect the likelihood of financial distress of companies. This research falls into the third stage of TKT measurement, which is the proof-of-concept of functions and/or important characteristics analytically and experimentally. This type of research employs a quantitative approach method with combined time series and cross-sectional data (Panel Data). The data collection technique used is secondary data collection, where data is collected from previously existing data. The sample companies in Indonesia listed on the IDX during the period 2019 to 2022. The data analysis method uses the Eviews 12 analysis tool. Research on the characteristics of the Board of Directors and its impact on the financial distress of companies can provide valuable insights into how corporate practices and financial decision-making contribute to the achievement of sustainable development goals (SDGs-8). Based on the research results, it was found that from all the characteristics of the board of directors measured, the accounting expertise possessed by the board of directors had a negative effect on the Company's financial difficulties. While other characteristics did not affect the Company's financial difficulties.